The Synergy Effect: Managerial Competence and Work Motivation in Teacher Performance - Renny Octavia; Alhadi Yan Putra; Pahlawan Pahlawan (Journal of Educational Sciences, 2026)
This study aims to analyze the influence of principals’ managerial competence and work motivation on teacher performance in senior and vocational high schools in Pemulutan District. Using a quantitative approach with an ex post facto design, the research involved 81 teachers through census technique. Data collection instruments consisted of validated Likert-scale questionnaires (r>0.374; α>0.90). Data analysis employed Spearman correlation and multiple linear regression. Based on the analysis, principals’ managerial competence has a positive and significant effect on teacher performance with a moderate contribution, while work motivation shows a stronger and more dominant positive influence with a higher contribution. Simultaneously, both variables significantly affect teacher performance with a strong combined contribution and a small synergistic effect. The regression equation further indicates that work motivation has a greater impact than managerial competence, making it the most influential factor in improving teacher performance. Managerial implications: principals need to optimize managerial competence while facilitating the development of teachers’ work motivation to enhance education quality.